A study of the morphological characteristics and patterns of starch grains in three species of the genus Arum L. - جديد لما; دينا حداد; سمير طباش (Latakia University Journal -Biological Sciences Series, 2023)
Three species belonging to the genus Arum L. were collected from lattakia region are: A. palaestinum, A. dioscoridis, and A. italicum. The study included the plant’s habit, tubers, leaves, inflorescence, spathe, flowers ( male, female, sterile ), fruit, and seed. The patterns of starch granules for the tubers were also determined using distinctive morphological criteria (Shape, Hilum, Lamellae, Oblong central cavity, Fissures, sizes) It varied between spherical, hemispherical, rectangular, triangular, rhomboid, Trapeziform, polygonal. The hilum was central in starch granules for the studied species, the Fissures were visible in the spherical shape only in Arum palaestinum and A. dioscoridis in the shape of a Y, the Oblong central cavity it was found in the spherical shape at Arum palaestinum . The sizes of starch grains were distributed in two patterns are, type A, and the largest starch grain size was 12 * 14 µm for the Trapeziform shape for Arum palaestinum, and for the type B, it was the smallest starch grain and amounted to 6 * 7 µm, which distinguished the triangular shape in Arum palaestinum